Globalization and the Economic Report of the President - Hanson, Gordon (Journal of Economic Literature, 2005)
T here are two chapters in the ERP that deal with globalization, one on immigration and another on international trade. Both are topics that have given the Bush Administration heartburn. Before 9/11, the administration upset Republican lawmakers by suggesting it might endorse an amnesty to illegal immigrants. After 9/11, and the discovery that several of the hijackers were in the country illegally, discussion of an amnesty was quietly shelved. On trade, the first Bush term witnessed conflict with Europe over U.S. tariffs on imported steel and tax subsidies to U.S. exporters, outcry over former CEA chairman Gregory Mankiw's approving remarks on global outsourcing by U.S. companies, and battles in Congress over the Central American Free Trade Agreement and other proposed trade treaties. This legacy may account for the somewhat defensive tone the